How Gender Stereotypes Impact Health Information Seeking Intention: Insights from an Implicit Association Test - Chia-Heng Chang (Taylor & Francis Group, 2021)
The social construction of gender has profound implications on how individuals of different gender identities perceive health and formulate health-related decisions. An online survey experiment (N = 262) was conducted using implicit association test (IAT) to examine gender stereotypes on two preventative health behaviors—lung cancer screening and family planning—and how these stereotypes interact with gender identity to impact information-seeking intentions. Lung cancer screening was viewed to be significantly more related to men, while family planning was more linked to women. Female participants showed stronger stereotypical perceptions regarding the two preventive behaviors than their male counterparts. While both male and female participants who believed more in the gender stereotype on lung cancer screening reported decreased intention to seek relevant health information, gender stereotypes interacted with participant gender identity in influencing intention to seek information on family planning. Theoretical and practical implications are discussed.